Architectural plan of transcriptional regulation in Mycobacterium tuberculosis. Issue 3 (March 2015) - Baloni, Priyanka; Chandra, Nagasuma
<x xml:space="preserve">Abstract</x> Transcriptional regulation enables adaptation in bacteria. Typically, only a few transcriptional events are well understood, leaving many others unidentified. The recent genome-wide identification of transcription factor binding sites in Mycobacterium tuberculosis has changed this by deciphering a molecular road-map of transcriptional control, indicating active events and their immediate downstream effects.